Congenital Rubella Syndrome as a possible cause for persistent thrombocytopenia in early infancy: The Forgotten Culprit - Kumar, Jogender; Sundaram, Venkataseshan; Gupta, Kirti; Bhatia, Anmol; Kaur, Gurwinder; Dutta, Sourabh (Autopsy and Case Reports, 2022)
We present a case of a late preterm intrauterine growth-restricted neonate with isolated and persistent severe thrombocytopenia. At birth, the neonate did not have a complete clinical spectrum of congenital rubella syndrome (CRS) but later developed peculiar findings that helped clinch the diagnosis. The neonate also had interstitial pneumonia and died secondary to superimposed acute viral infection leading to acute respiratory distress syndrome. The serology was positive for IgM antibodies against the rubella virus. The constellation of clinical manifestations of congenital rubella in the presence of positive IgM antibody against rubella and consistent histopathology confirmed the diagnosis of CRS.